Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI 2020-2023) - Deswinta Yulia Putri; Lili Wahyuni; Rita Dwi Putri (Politeknik Raflesia Press, 2025)
This study was conducted because several previous studies on the variables of Liquidity and Company Size on Company Financial Performance produced different findings so that they are interesting to review. This type of research is quantitative research, where the review of the explanation level is associative research with a causal relationship. The unit of analysis in this study is the Food and Beverage sub-sector companies listed on the IDX for the period 2020-2023. The population in this study was 42 companies and the number of samples was 24 companies, so there were 96 samples. The results of this study indicate that Liquidity does not affect the Company's Financial Performance, Company Size does not affect the Company's Financial Performance and Liquidity and Company Size do not affect the Company's Financial Performance.